Method for manufacturing polarizing plate

By bonding an optical film on the polarizer and humidifying treatment, the problem of easy cracks and deiodation of the ends of the polarizer in the prior art in thermal shock tests is solved, and the polarization performance stability under low and high temperature conditions is achieved.

CN114391115BActive Publication Date: 2025-04-01SUMITOMO CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080063665.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-12
Filing Date
2020-08-06
Publication Date
2025-04-01
Estimated Expiration
2040-08-06

AI Technical Summary

Technical Problem

The prior art is prone to cracks in repeated low-temperature and high-temperature thermal shock tests, and there is deiodation in the end area of ​​the polarizer, affecting the polarization performance.

Method used

A manufacturing method is adopted in which an optical film is bonded to one side of a polarizer having a thickness of 15 μm or less and a humidification treatment is performed. The specific steps include a first lamination process and a humidification process, and maintain the first laminate under a temperature of 35°C or higher and a humidity of 75% RH or higher to remove excess boric acid at the end of the polarizer without deiodation.

Benefits of technology

It effectively suppresses the generation of cracks in repeated low-temperature and high-temperature thermal shock tests, and maintains linear polarization ability in the end area of ​​the polarizer, avoiding deiodation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114391115B_ABST
    Figure CN114391115B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a polarizing plate, which suppresses the generation of cracks in a thermal shock test under repeated low temperature (-40°C) conditions and high temperature (85°C) conditions, and does not produce deiodination in a region including an end portion. The method for manufacturing a polarizing plate of the present invention comprises: a first lamination step, in which an optical film is laminated on at least one side of a polarizer having a thickness of less than 15 μm to produce a first laminate; and a humidification treatment step, in which the first laminate is maintained in a gas phase at a temperature of more than 35°C and a relative humidity of more than 75%RH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a polarizing plate, and further relates to a polarizing sheet, a polarizing plate and an image display device including the polarizing plate. Background Art

[0002] Patent Document 1 proposes a method for producing a polarizing plate having a portion with a low boric acid concentration formed at an edge thereof by bringing the polarizing plate into contact with a treatment liquid at 50° C. or higher.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-206641 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the manufacturing method described in Patent Document 1, when viewed from above the portion of the polarizer that is in contact with a treatment liquid at a temperature above 50°C, a portion with a low concentration of boric acid is formed at the end and in the entire region from the end to a distance of more than 50 μm, and deiodination occurs at the end and from the end over a range of more than 300 μm.

[0008] The object of the present invention is to provide a method for manufacturing a polarizing plate, wherein the method suppresses the generation of cracks in a thermal shock test under repeated low temperature (-40°C) and high temperature (85°C) conditions, and does not produce deiodination in a region including an end portion. In addition, another object of the present invention is to provide a polarizer that suppresses cracks and does not produce deiodination in a region including an end portion, and a polarizing plate including the polarizer.

[0009] Means for solving problems

[0010] The present invention provides the following method for producing a polarizing plate, a polarizing sheet, a polarizing plate, and an image display device.

[0011] [1] A method for manufacturing a polarizing plate, comprising:

[0012] a first lamination step of laminating an optical film on at least one side of a polarizing plate having a thickness of 15 μm or less to produce a first laminate; and

[0013] In the humidification treatment step, the first laminate is maintained in a gas phase at a temperature of 35° C. or higher and a relative humidity of 75% RH or higher.

[0014] [2] The method for producing a polarizing plate according to [1], further comprising a molding step of molding the first stack before the humidification step.

[0015] [3] The method for producing a polarizing plate according to [2], wherein in the forming step, a non-uniform portion is formed in the first laminate.

[0016] [4] The method for producing a polarizing plate according to [2] or [3], further comprising a cutting step of cutting the first stack before the humidification step.

[0017] [5] The method for manufacturing a polarizing plate according to [4], wherein, in the cutting step, the first stack is cut in a manner such that the position of the end of the optical film is the same as the position of the end of the polarizer when viewed from above.

[0018] [6] A polarizing plate comprising a resin film containing boric acid and iodine and having a thickness of 15 μm or less,

[0019] The polarizing plate has a region including an end portion, wherein the region contains boric acid at a concentration lower than the concentration of boric acid in regions other than the region.

[0020] No deiodination occurs in the region including the end portion of the polarizer.

[0021] [7] A polarizing plate comprising the polarizing plate according to [6], and an optical film bonded to at least one side of the polarizing plate.

[0022] [8] The polarizing plate according to [7], wherein, at the end of the polarizing plate in a plan view, the position of the end of the polarizer is the same as the position of the end of the optical film.

[0023] [9] An image display device comprising the polarizing plate described in [8].

[0024]

[10] The image display device according to [9], which has a camera hole.

[0025] Effects of the Invention

[0026] According to the present invention, a method for manufacturing a polarizing plate can be provided, wherein the method suppresses the generation of cracks in a thermal shock test under repeated low temperature (-40°C) conditions and high temperature (85°C) conditions, and does not produce deiodination in a region including an end portion. In addition, according to the present invention, a polarizing plate can be provided, wherein cracks are suppressed in a thermal shock test under repeated low temperature (-40°C) conditions and high temperature (85°C) conditions (hereinafter also referred to as a thermal shock test for simplicity), and deiodination is not produced in a region including an end portion, and a polarizing plate including the polarizing plate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1This is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention.

[0028] Figure 2 It is a schematic diagram showing an example of the first stacked body.

[0029] Figure 3 This is a schematic plan view of a polarizing plate for explaining a low boric acid concentration portion.

[0030] Figure 4 This is a schematic cross-sectional view showing an example of an image display device having a camera hole.

[0031] Figure 5 It is a schematic diagram showing an example of the second stacked body and the end mill.

[0032] Figure 6 This is a schematic diagram showing an example of a cutting process.

[0033] Figure 7 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0034] Figure 8 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0035] Fig. 9 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.

[0036] Fig.10 This is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention.

[0037] Fig.11 It is a schematic diagram for explaining the measurement sample of the Example.

[0038] Fig.12 The TOF-SIMS analysis results of the polarizing plate of Example 2 are shown.

[0039] Fig.13 The results of observing the end portion of the polarizing plate of Example 2 are shown.

[0040] Fig.14 The results of observation of the end portion of the polarizing plate of Comparative Example 3 are shown. DETAILED DESCRIPTION

[0041] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to the following embodiments. In all the following drawings, in order to facilitate the understanding of each component, the proportions of the components shown in the drawings are appropriately adjusted, and the proportions of the components shown in the drawings are not necessarily consistent with the proportions of the actual components. In the accompanying drawings, the same symbols are added to the same components. The X, Y and Z shown in each figure represent three mutually orthogonal coordinate axes. The directions shown by the XYZ coordinate axes in each figure are common in each figure.

[0042] <Method for producing polarizing plate>

[0043] A method for manufacturing a polarizing plate according to one embodiment of the present invention comprises: a first lamination step of laminating an optical film on at least one side of a polarizer having a thickness of less than 15 μm to produce a first laminate; and a humidification treatment step of maintaining the first laminate in a gas phase at a temperature of more than 35° C. and a relative humidity of more than 75% RH.

[0044] The polarizing plate obtained by the method for manufacturing a polarizing plate may have optical films on both sides of the polarizer. Figure 1 As shown, the polarizing plate 1 includes a polarizer 2 disposed between a first optical film 3 and a second optical film 4. Hereinafter, the first optical film and the second optical film may be collectively referred to as an optical film or a pair of optical films.

[0045] (First Lamination Step)

[0046] In the first lamination step, the polarizing plate and the optical film are overlapped and bonded to each other to produce the first laminate. The polarizing plate and the optical film may be in the form of long strips. In the case where the polarizing plate is arranged between a pair of optical films and overlapped, as Figure 2 As shown, in the first laminate 10, the polarizer 7 is located between a pair of the first optical film 5 and the second optical film 9. The optical film may be bonded to the polarizer via an adhesive layer containing an adhesive.

[0047] (Polarizing Plate)

[0048] The polarizing plate may be one in which, for example, iodine is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film, and polyvinyl alcohol molecular chains are cross-linked with boric acid.

[0049] The polarizing plate may be an absorption-type polarizing plate having the property of absorbing linearly polarized light having a vibration plane parallel to the absorption axis and transmitting linearly polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis).

[0050] The polarizer can be manufactured, for example, by stretching, dyeing, and crosslinking a polyvinyl alcohol resin film (hereinafter also referred to as a PVA film). The stretching, dyeing, and crosslinking can be performed using known methods. The polyvinyl alcohol resin film can be in the form of a long strip or a paper.

[0051] For example, first, the PVA film is stretched in a uniaxial direction or a biaxial direction. The polarizer stretched in a uniaxial direction has a tendency to have a high dichroic ratio. After stretching, the PVA film is dyed with iodine, dichroic pigment (polyiodine) or organic dye using a dyeing solution. The dyeing solution may contain boric acid, zinc sulfate, or zinc chloride. The PVA film may be washed with water before dyeing. By washing with water, dirt and anti-blocking agents are removed from the surface of the PVA film. In addition, the PVA film swells due to washing with water, and as a result, it is easy to suppress uneven dyeing (uneven dyeing). In order to crosslink the dyed PVA film, the dyed PVA film is treated with a solution of a crosslinking agent containing boric acid (e.g., an aqueous solution of boric acid). After the treatment with the crosslinking agent, the PVA film is washed with water and then dried. After the above steps, a polarizer containing a resin film containing boric acid and iodine is obtained. The polyvinyl alcohol (PVA) resin is obtained by saponifying a polyvinyl acetate resin. The polyvinyl acetate resin may be, for example, polyvinyl acetate which is a homopolymer of vinyl acetate, or a copolymer of vinyl acetate and other monomers (e.g., ethylene-vinyl acetate copolymer). Other monomers copolymerized with vinyl acetate may be ethylene, and may also be unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, or acrylamides having an ammonium group. The polyvinyl alcohol resin may also be modified by aldehydes. The modified polyvinyl alcohol resin may be, for example, partially formalized polyvinyl alcohol, polyvinyl acetal, or polyvinyl butyral. The polyvinyl alcohol resin may be a polyene oriented film such as a dehydrated product of polyvinyl alcohol or a dehydrochlorinated product of polyvinyl chloride. It may be dyed before stretching, or it may be stretched in a dyeing solution. The length of the stretched resin film may be, for example, 3 to 7 times the length before stretching.

[0052] The thickness of the polarizer can be, for example, 15 μm or less, preferably 10 μm or less, and more preferably 8 μm or less. The thickness of the polarizer is usually 1 μm or more, for example, 3 μm or more. The thinner the polarizer, the easier it is to suppress the contraction or expansion of the polarizer itself with temperature changes, and there is a tendency to easily suppress the change in the size of the polarizer itself. As a result, it is difficult to apply stress to the polarizer, and there is a tendency to easily suppress cracks in the polarizer.

[0053] (Optical Film)

[0054] The optical film may be a light-transmitting thermoplastic resin. The optical film may be an optically transparent thermoplastic resin. The resin forming the optical film may be, for example, a chain polyolefin resin, a cyclic olefin polymer resin (COP resin), a cellulose ester resin, a polyester resin, a polycarbonate resin, a (meth) acrylic resin, a polystyrene resin, or a mixture or copolymer thereof.

[0055] In the case where the polarizing plate has the first optical film and the second optical film, the composition of the first optical film can be completely the same as the composition of the second optical film. For example, the first optical film and the second optical film can both contain cyclic olefin polymer resin (COP resin). In the case where the first optical film and the second optical film contain cyclic olefin polymer resin (COP resin), it is easy to obtain the effect of the present invention. In the case where the polarizing plate has the first optical film and the second optical film, the composition of the first optical film can be different from the composition of the second optical film.

[0056] The glass transition temperature of the first optical film and the second optical film is preferably 100° C. to 200° C., or 120° C. to 150° C. When the glass transition temperature of each of the first optical film and the second optical film is within the above range, the first optical film and the second optical film are easily fused to each other due to the heat generated by grinding the end portions of each optical film.

[0057] The chain polyolefin-based resin may be, for example, a homopolymer of a chain olefin such as polyethylene resin or polypropylene resin, or a copolymer containing two or more chain olefins.

[0058] Cyclic olefin polymer resins (cyclic polyolefin resins) may be, for example, ring-opening (co)polymers of cyclic olefins, or addition polymers of cyclic olefins. Cyclic olefin polymer resins may be, for example, copolymers (e.g., random copolymers) of cyclic olefins and chain olefins. The chain olefins forming the copolymers may be, for example, ethylene or propylene. Cyclic olefin polymer resins may be graft polymers obtained by modifying the above-mentioned polymers with unsaturated carboxylic acids or their derivatives, or their hydrogenates. Cyclic olefin polymer resins may be, for example, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers.

[0059] The cellulose ester resin may be, for example, cellulose triacetate (triacetylcellulose (TAC)), cellulose diacetate, cellulose tripropionate or cellulose dipropionate. Copolymers thereof may also be used. Cellulose ester resins in which a part of the hydroxyl groups is modified with other substituents may also be used.

[0060] Polyester resins other than cellulose ester resins may also be used. The polyester resin may be, for example, a polycondensate of a polycarboxylic acid or a derivative thereof and a polyol. The polycarboxylic acid or a derivative thereof may be a dicarboxylic acid or a derivative thereof. The polycarboxylic acid or a derivative thereof may be, for example, terephthalic acid, isophthalic acid, dimethyl terephthalate, or dimethyl naphthalate. The polyol may be, for example, a diol. The polyol may be, for example, ethylene glycol, propylene glycol, butanediol, neopentyl glycol, or cyclohexanedimethanol.

[0061] The polyester resin may be, for example, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polycyclohexanedimethylene terephthalate, or polycyclohexanedimethylene naphthalate.

[0062] The polycarbonate resin is a polymer obtained by bonding polymer units (monomers) via carbonate groups. The polycarbonate resin may be a modified polycarbonate having a modified polymer skeleton or a copolymer polycarbonate.

[0063] The (meth)acrylic resin may be, for example, poly(meth)acrylate (e.g., polymethyl methacrylate (PMMA)); methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylate-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (e.g., MS resin); copolymers of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.).

[0064] The first optical film or the second optical film may each contain at least one additive selected from the group consisting of a lubricant, a plasticizer, a dispersant, a heat stabilizer, an ultraviolet absorber, an infrared absorber, an antistatic agent, and an antioxidant.

[0065] The thickness of the first optical film may be, for example, 5 μm to 90 μm, or 10 μm to 60 μm. The thickness of the second optical film may also be, for example, 5 μm to 90 μm, or 10 μm to 60 μm.

[0066] At least one of the first optical film and the second optical film may be a film having an optical function. The film having an optical function may be, for example, a phase difference film or a brightness enhancement film. For example, a phase difference film having an arbitrary phase difference value may be obtained by stretching the film containing the thermoplastic resin or forming a liquid crystal layer on the film.

[0067] The first optical film may be overlapped with the polarizer via an adhesive layer. The second optical film may also be overlapped with the polarizer on the side opposite to the first optical film via an adhesive layer. The adhesive layer may include an aqueous adhesive such as polyvinyl alcohol. The adhesive layer may also include an active energy ray-curable resin described later.

[0068] The active energy ray-curable resin is a resin that is cured by being irradiated with active energy rays. The active energy rays may be, for example, ultraviolet rays, visible light, electron beams, or X-rays. For example, the active energy ray-curable resin may be an ultraviolet-curable resin.

[0069] The active energy ray-curable resin may be a single resin or may contain multiple resins. For example, the active energy ray-curable resin may contain a cationically polymerizable curable compound or a radically polymerizable curable compound. The active energy ray-curable resin may contain a cationically polymerizable initiator or a radically polymerizable initiator for initiating a curing reaction of the curable compound.

[0070] The cationically polymerizable curable compound may be, for example, an epoxy compound (a compound having at least one epoxy group in the molecule) or an oxetane compound (a compound having at least one oxetane ring in the molecule). The radically polymerizable curable compound may be, for example, a (meth)acrylic compound (a compound having at least one (meth)acryloyloxy group in the molecule). The radically polymerizable curable compound may also be a vinyl compound having a radically polymerizable double bond.

[0071] The active energy ray-curable resin may contain a cationic polymerization accelerator, an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow regulator, a plasticizer, a defoamer, an antistatic agent, a leveling agent, or a solvent, etc., as necessary.

[0072] (Humidification treatment process)

[0073] The first stack is maintained in a gas phase at a temperature of 35°C or above and a relative humidity of 75%RH or above, thereby performing a humidification treatment. According to the humidification treatment, in the region including the end of the first stack, although a region containing boric acid (hereinafter also referred to as a low-boric acid region) is formed at a concentration lower than the concentration of boric acid in the region outside the region, deiodination does not occur, so that linear polarization capability can be exerted in the low-boric acid region. The polarizing plate manufactured by the manufacturing method of the present invention does not produce cracks in a thermal shock test, and can also exert linear polarization capability in the region including the end.

[0074] It is known that, as described in Patent Document 1, in order to suppress the generation of cracks in a thermal shock test, it is effective to reduce the concentration of boric acid contained in the end of the polarizer. However, it was found that in the manufacturing method described in Patent Document 1, boric acid is removed from the end of the polarizer and all regions from the end to a distance of more than 50 μm, resulting in deiodination occurring in the end of the polarizer and all regions with a width greater than 300 μm from the end, and the linear polarization capability cannot be exerted at the end. However, according to the manufacturing method of the present invention, only the excess boric acid contained in the end of the polarizer is removed by performing a humidification treatment maintained in a gas phase at a temperature of more than 35°C and a relative humidity of more than 75%RH, and there is a tendency that deiodination is not easy to occur, so the resulting polarizing plate can suppress the generation of cracks in a thermal shock test and can also exert linear polarization capability at the end.

[0075] The concentration of boric acid is the concentration of boric acid per unit area including the thickness direction of the polarizing plate, and is measured, for example, by time-of-flight secondary ion mass spectrometry (TOF-SIMS) described in the Example column below. In this specification, boric acid contains, for example, boric acid molecules (H3BO3) and boric acid ions (BO3 3- ).

[0076] The region where deiodination occurs (hereinafter also referred to as the deiodination region) is a region visually observed as a region through which light is transmitted using a polarizing microscope under crossed Nicol prisms. Iodine includes, for example, iodine molecules (I2), polyiodine complexes (I3 - 、I5 - ), iodide ion (I - ).

[0077] In this specification, the term "planar view" means viewing from the thickness direction of the polarizing plate.

[0078] The temperature of the gas phase is 35°C or higher. By setting the temperature of the gas phase to 35°C or higher, there is a tendency to easily remove excess boric acid contained in the end of the polarizing plate. From the viewpoint of easily removing boric acid, the temperature of the gas phase is preferably 40°C or higher. The temperature of the gas phase may be, for example, 90°C or lower, preferably 85°C or lower. When the temperature of the gas phase is 90°C or lower, there is a tendency that deiodination is not easily generated. The temperature of the gas phase may be adjusted within the above range so that excess boric acid is removed at the end of the polarizing plate and deiodination does not occur.

[0079] The relative humidity of the gas phase is 75% RH or more. By making the relative humidity 75% RH or more, there is a tendency to easily remove the excess boric acid contained in the end of the polarizer. From the viewpoint of easy removal of boric acid, the relative humidity of the gas phase is preferably 80% RH or more. The relative humidity of the gas phase can be, for example, 90% RH or less, preferably 85% RH or less. When the relative humidity of the gas phase is 90% RH or less, there is a tendency that deiodination is not easy to occur. The relative humidity of the gas phase can be adjusted within the above range so that excess boric acid is removed at the end of the polarizer and deiodination does not occur.

[0080] The time for humidification treatment can be, for example, more than 0.5 hour and less than 4 hours, from the viewpoint of easy removal of boric acid and anti-deiodination, more than 1 hour and less than 3 hours, more preferably more than 1.5 hours and less than 2.5 hours. In addition, humidification treatment is usually carried out continuously for the above-mentioned time.

[0081] The humidification treatment can be performed using, for example, a constant temperature and humidity oven.

[0082] When the first laminate has a deformed portion described below, it is preferred to perform a humidification treatment on an edge region included in the deformed portion from the viewpoint of suppressing cracks and making deiodination less noticeable.

[0083] From the viewpoint of suppressing cracks and making deiodination less noticeable in the appearance of the polarizing plate, it is preferred to perform the humidification treatment in such a manner that the concentration of boric acid in the low-boric acid-containing region is higher as it moves away from the end in the inner direction from the end of the polarizing plate. Under the conditions of the humidification treatment, it is easy to obtain such a concentration when the temperature of the gas phase is lowered, the relative humidity is lowered, and the time for the humidification treatment is shortened.

[0084] The low-boric acid region can be formed, for example, in a region greater than 15 μm in the inner direction from the end portion of the polarizing plate when viewed from above. From the viewpoint of suppressing cracks, it is preferably formed in a region greater than 15 μm and less than 200 μm, more preferably in a region greater than 20 μm and less than 150 μm, further preferably in a region greater than 20 μm and less than 100 μm, and particularly preferably in a region greater than 20 μm and less than 50 μm.

[0085] The low-boric acid content region may be formed in a region that is 15 μm or less from the edge of the polarizing plate in a plan view.

[0086] The low-boric acid region can be continuously formed in all regions with a distance of less than 15 μm from the end of the polarizing plate in a top view, and in all regions with a distance greater than 15 μm and less than 200 μm in the inner direction from the end of the polarizing plate in a top view. In other words, the low-boric acid region can be formed in all regions between the end of the polarizing plate in a top view and the distance less than 200 μm from the end. In the case where the low-boric acid region is formed in all regions between the end of the polarizing plate in a top view and the distance less than 200 μm from the end, the boundary between the low-boric acid region and the region other than the region can exist in the region between the end and the distance less than 200 μm from the end.

[0087] The low-boric acid region is preferably formed in the entire region between the end of the polarizing plate when viewed from above and a distance of less than 100 μm from the end, more preferably formed in the entire region between the end of the polarizing plate when viewed from above and a distance of less than 50 μm from the end, and further preferably formed in the entire region between the end of the polarizing plate when viewed from above and a distance of less than 20 μm from the end.

[0088] The end portion of the polarizing plate does not need to contain boric acid.

[0089] The boundary between the region with low boric acid content and the region outside the region can be obtained, for example, according to the boric acid concentration distribution relative to the distance from the end obtained in the time-of-flight secondary ion mass spectrometry (TOF-SIMS) described in the first column of the embodiment described later. For example, in the case of a region where the boric acid ion strength is constant and can be read in the boric acid concentration distribution, the average value of the boric acid ion strength in the region is obtained, and the position from the end to the position where the boric acid ion strength is the above average value is set as a low boric acid concentration portion. In the case of a region where it is difficult to read the above-mentioned boric acid ion strength constant in the boric acid concentration distribution, in the boric acid concentration distribution, the average value of the boric acid ion strength in the range of 30 μm inside the point where the boric acid ion strength is the largest is obtained, and the position from the end to the position where the boric acid ion strength is the above average value is set as a low boric acid concentration portion.

[0090] The low-boric acid-containing region may be one continuous region or may be divided into a plurality of regions in a plan view of the polarizing plate.

[0091] From the viewpoint of crack suppression, the low-boric acid region is preferably formed along the outer edge of the polarizing plate. The low-boric acid region may be formed along the entire outer edge of the polarizing plate or may be formed along a portion of the outer edge of the polarizing plate.

[0092] By performing such humidification treatment, a polarizer can be obtained, wherein the end portion of the polarizer when viewed from above has a region containing boric acid at a concentration lower than the concentration of boric acid in regions other than the region. Specifically, the polarizer is a polarizer formed with a low boric acid concentration portion, and the concentration of boric acid in the low boric acid concentration portion is lower than the concentration of boric acid in the inner region at 500 μm or more from the end portion. In the inner region, the concentration of boric acid may be substantially the same. Figure 3 The polarizer 2 shown may have a low boric acid concentration portion 30 in a region including an end portion when viewed from above, and an inner region 32 at an inner side of more than 500 μm from the end portion. The inner region 32 may include an area for displaying an image when incorporated into a liquid crystal display device. The boric acid concentration in the intermediate region 31 between the low boric acid concentration portion 30 and the inner region 32 is generally substantially the same as that in the inner region 32. In addition, by implementing the humidification treatment, a polarizer can be obtained in which deiodination does not occur at the end portion of the polarizer when viewed from above. Specifically, the polarizer is a polarizer in which a low iodine concentration portion is not formed, and the low iodine concentration portion refers to a portion where the concentration of iodine is lower than that in the above-mentioned inner region.

[0093] (Forming process)

[0094] The method for manufacturing a polarizing plate may further include a forming step of forming the first stack before the humidification treatment step. In the forming step, the first stack may be formed into a predetermined shape by cutting and / or punching. The cutting and / or punching may be performed by using a cutter or irradiating a laser. The laser may be a CO2 laser.

[0095] For the first stack, the size of the first stack can be adjusted to a size that is easy to process by a forming process. In addition, a special-shaped portion can be formed on the outer edge of the first stack by punching or cutting. The special-shaped portion can be, for example, a concave portion formed on the outer edge, a V-shaped portion protruding inwardly, and a through hole formed in the surface when the first stack is viewed from above. The first stack can have more than two special-shaped portions on the outer edge and / or in the surface. The through hole formed in the surface can be the above-mentioned camera hole, etc.

[0096] The polarizing plate with the irregular portion is prone to stress concentration in the irregular portion during a thermal shock test, and tends to be prone to cracking. Although the polarizing plate of the present invention has the irregular portion, the low-boric acid-containing region is formed in the end region of the irregular portion, which tends to suppress the generation of cracks during a thermal shock test.

[0097] The polarizing plate manufactured by the manufacturing method of the present invention is suitable for, for example, an image display device having a camera hole. Figure 4In the image display device 20 shown with a camera hole 22, a cover glass 24, an adhesive layer 25, a polarizing plate 21, a liquid crystal panel 23, a polarizing plate 26, a camera 27, and a light-shielding tape 28, the portion of the camera hole surrounded by a circle in the figure is easily observed directly. If deiodination occurs in such a portion, the deiodination tends to become conspicuous, and as a result, there is a situation in which the design is reduced. However, since the polarizing plate of the present invention does not produce deiodination in the region including the end, even when it is arranged on the visible side in the image display device, deiodination is not easy to be conspicuous, and it is not easy to produce a reduction in design.

[0098] When the irregularly shaped portion is a concave portion, from the viewpoint of suppressing cracks, it is preferred that the depth direction of the concave portion is orthogonal to the absorption axis (stretching axis direction). Alternatively, the concave portion may be formed so that its depth direction intersects the absorption axis (stretching axis direction) at an angle of generally 30° or more and 60° or less.

[0099] (Cutting process)

[0100] The method for manufacturing a polarizing plate may further include a cutting step before the humidification treatment step, wherein an end mill is brought into contact with the outer periphery of the first stack or the second stack described later, and the end mill is moved along the outer periphery of the stack. Figure 2 As shown, the positions of the ends of the polarizing plate 7, the first optical film 5, and the second optical film 9 can be aligned over the entire periphery of the first laminate 10 before the cutting step.

[0101] like Figure 5 and Figure 6 As shown in FIG. 1 , the end mill 50 used in the cutting process has a protruding blade (edge) 50e on the side surface substantially parallel to the rotation axis 50a thereof. In the cutting process, the side surface of the end mill 50 is brought into contact with the outer periphery (end surface) of the first stack 10, and the rotating end mill 50 is moved along the outer periphery of the first stack 10. For example, the rotating end mill 50 may be moved along the outer periphery of the first stack 10. Figure 6 As a result, the outer periphery (end face) of the first stack 10 is cut or polished by the blade 50e, and the outer periphery (end face) of the first stack 10 becomes smooth, forming a concave portion 13, and the inner corner of the concave portion 13 is chamfered. Figure 5 As shown, after a plurality of first stacks 10 are stacked to form a second stack 100, the side surface of the end mill 50 is brought into contact with the outer periphery (end surface) of the second stack 100, and the rotating end mill 50 is moved along the outer periphery of the second stack 100. That is, in the cutting process, the outer peripheries of the plurality of first stacks 10 forming the second stack 100 can be cut or ground at once with the end mill 50. In the cutting process, the corners at both ends of the concave portion 13 and the corners at the four corners of the first stack 10 can each be chamfered.

[0102] The amount of cutting by the end mill in the cutting step may be, for example, 10 μm or more and 500 μm or less, and preferably 50 μm or more and 150 μm or less.

[0103] The cutting process may be repeated three or more times. For example, in the third cutting process, the first stack 10 is basically not cut, but the chips generated in the second cutting process are removed from the end surface of the first stack 10. In each cutting process, a plurality of end mills may be used.

[0104] The feed rate of the end mill in the cutting process can be 100 mm / min or more and less than 3000 mm / min. The rotation speed of the end mill in the cutting process can be, for example, 500 rpm or more and 60000 rpm or less, preferably 10000 rpm or more and 60000 rpm or less. The cutting angle in the cutting process can be, for example, 30° or more and 70° or less, preferably 45° or more and 65° or less. When the helix angle of the end mill 50 is α, the cutting angle β is defined as 90°-α. Figure 6 As shown, the helix angle α of the end mill 50 is the angle formed by the direction d1 in which the blade 50e extends on the side of the end mill 50 and the rotation axis 50a of the end mill 50. The cutting angle β can also be changed to the angle formed by the direction d1 in which the blade 50e extends and the direction d2 perpendicular to the rotation axis 50a. The diameter φ (thickness) of the end mill 50 used in the cutting process can be, for example, 3.0 mm or more and 6.0 mm or less.

[0105] By performing cutting processing in the state of the first laminate or the second laminate, the first laminate or the second laminate can be cut in a manner such that the position of the end of the optical film is the same as the position of the end of the polarizer when viewed from above the first laminate or the second laminate. Therefore, the obtained polarizing plate can have linear polarization capability up to the end of the polarizing plate at the end formed by cutting processing.

[0106] <Polarizing Plate>

[0107] Another embodiment of the polarizer of the present invention is a polarizer comprising a resin film containing boric acid and iodine and having a thickness of 15 μm or less. The polarizer may be, for example, a polarizer in which iodine is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol resin film, and the polyvinyl alcohol molecular chains are cross-linked by boric acid. The polarizer may be an absorption-type polarizer having the following properties, that is, absorbing linear polarized light having a vibration plane parallel to the absorption axis and transmitting linear polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis).

[0108] The polarizer is a polarizer that has a region containing boric acid at a concentration lower than the concentration of boric acid in the region outside the region (hereinafter also referred to as the low boric acid region of the polarizer) in the region including the end of the polarizer, and does not produce deiodination in the region including the end of the polarizer. Therefore, the polarizer of the present invention can suppress the generation of cracks in a thermal shock test, and can also exert linear polarization capability even at the end.

[0109] From the viewpoint of suppressing cracks and making deiodination less noticeable in the appearance of the polarizer, the concentration of boric acid in the low-boric acid region of the polarizer is preferably higher as it moves away from the end of the polarizing plate in the inner direction.

[0110] The low-boric acid region of the polarizer can be formed, for example, in a region greater than 15 μm in the inner direction from the end portion when viewed from above the polarizer. From the viewpoint of suppressing cracks, it can be preferably formed in a region greater than 15 μm and less than 200 μm, more preferably in a region greater than 20 μm and less than 150 μm, further preferably in a region greater than 20 μm and less than 100 μm, and particularly preferably in a region greater than 20 μm and less than 50 μm.

[0111] The low-boric acid-containing region of the polarizing plate may be formed in a region that is 15 μm or less from the edge of the polarizing plate in a plan view.

[0112] The low-boric acid region of the polarizer can be continuously formed in all regions with a distance of less than 15 μm from the end of the polarizer when viewed from above, and in all regions with a distance greater than 15 μm and less than 200 μm in the inner direction from the end of the polarizer when viewed from above. In other words, the low-boric acid region of the polarizer can be formed in all regions between the end of the polarizer when viewed from above and the distance less than 200 μm from the end. In the case where the low-boric acid region of the polarizer is formed in all regions between the end of the polarizer when viewed from above and the distance less than 200 μm from the end, the boundary between the low-boric acid region of the polarizer and the region other than it can exist in the region between the end and the distance less than 200 μm from the end.

[0113] The low-boric acid region of the polarizer is preferably formed in the entire region between the end of the polarizer when viewed from above and a distance of less than 100 μm from the end, more preferably formed in the entire region between the end of the polarizer when viewed from above and a distance of less than 50 μm from the end, and further preferably formed in the entire region between the end of the polarizer when viewed from above and a distance of less than 20 μm from the end.

[0114] The end portion of the polarizer may not contain boric acid.

[0115] The boundary between the region where the low-boric acid-containing site is formed and the other regions can be determined by the method described in the above-mentioned method for producing a polarizing plate.

[0116] The low-boric acid-containing region of the polarizer may be one continuous region or may be divided into a plurality of regions when viewed from above the polarizer.

[0117] From the viewpoint of crack suppression, the low-boric acid region of the polarizer is preferably formed along the outer edge of the polarizer. The low-boric acid region may be formed along the entire outer edge of the polarizer or may be formed along a portion of the outer edge of the polarizer.

[0118] Specifically, the concentration of boric acid in the low-boric acid-containing region of the polarizer may be lower than the concentration of boric acid in the inner region 500 μm or more inward from the end. In the inner region, the concentration of boric acid may be substantially the same. Figure 3 As shown, the polarizer may have a low boric acid concentration portion 30 in a region including the end portion when viewed from above, and an inner region 32 at an inner side of more than 500 μm from the end portion. The inner region 32 may include an area for displaying an image when loaded into a liquid crystal display device. The boric acid concentration in the intermediate region 31 between the low boric acid concentration portion 30 and the inner region 32 is generally substantially the same as the boric acid concentration in the inner region 32. In addition, specifically, a polarizer that does not produce deiodination is a polarizer that does not form a low iodine concentration portion, and the low iodine concentration portion refers to a portion where the concentration of iodine is lower than the concentration of iodine in the above-mentioned inner region. The presence or absence of a low iodine concentration portion can be confirmed by the method for measuring in the first column of the embodiment described later.

[0119] The examples and preferred ranges of the thickness of the polarizer can be the same as those in the description of the method for producing the polarizing plate.

[0120] The polarizer may form a special-shaped portion at the outer edge. The special-shaped portion may be, for example, a concave portion formed at the outer edge, a V-shaped portion protruding inwardly, and a through hole formed in the surface when viewed from above the polarizer. The polarizer may have two or more special-shaped portions at the outer edge and / or in the surface. The through hole formed in the surface may be the camera hole mentioned above, etc. Since the polarizer does not produce deiodination in the region including the end, even when used in a polarizing plate arranged on the visible side in an image display device, it is not easy to make the deiodination conspicuous and it is not easy to reduce the design.

[0121] The polarizer can be produced, for example, by subjecting a uniaxially stretched polyvinyl alcohol-based resin film containing boric acid and iodine to a humidification treatment. Examples and preferred ranges of the humidification treatment conditions can be those described in the above-mentioned method for producing a polarizing plate.

[0122] <Polarizing plate>

[0123] A polarizing plate according to another embodiment of the present invention includes the above-mentioned polarizing plate and an optical film bonded to at least one side of the polarizing plate. The examples and preferred ranges of the optical film can be the same as those described in the above-mentioned method for producing the polarizing plate.

[0124] like Figure 1 As shown, the polarizing plate 1 of this embodiment includes at least one pair of optical films (3, 4) and a film-shaped polarizing plate 2 located between the pair of optical films (3, 4). In the following, for the convenience of description, the polarizing plate 1 formed by the polarizing plate 2 and the pair of optical films (3, 4) is mainly described. However, as described later, the number of optical films included in the polarizing plate is not limited to two.

[0125] An optical film refers to a film-like component that forms the polarizing plate 1 (excluding the polarizer 2 itself). For example, the optical film includes a protective film and a release film. Each optical film may not have a specific optical function when used alone. "Film" (optical film) can be renamed as "layer" (optical layer). A pair of optical films (3, 4) each contain a resin. However, the composition of each optical film (3, 4) is not limited. A pair of optical films (3, 4) each contain a resin. However, the composition of each optical film (3, 4) is not limited.

[0126] The polarizing plate 2 and the optical films (3, 4) are overlapped directly or indirectly. For example, another optical film may be present between the polarizing plate 2 and the optical films (3, 4). The polarizing plate 2 may be overlapped with the optical films (3, 4) via an adhesive layer.

[0127] Figure 7 The surface (light receiving surface) of the polarizing plate 1 of this embodiment is shown. Figure 7 The cross section of the polarizing plate 1 shown is perpendicular to the surface (light receiving surface) of the polarizing plate 1 , and is perpendicular to the outer periphery 1 p of the polarizing plate 1 located inside the recess 13 .

[0128] like Figure 7 As shown, the recess 13 is formed in the periphery 1p of the polarizing plate 1. That is, the recess 13 exists in the periphery 1p of the polarizing plate 1. The recess 13 may be referred to as a depression, a cutout or a notch. The recess 13 may penetrate the polarizing plate 1 in a direction (Z-axis direction) perpendicular to the surface (light-receiving surface) of the polarizing plate 1. The so-called periphery 1p of the polarizing plate 1 may be referred to as the outer edge or outline of the polarizing plate 1 (light-receiving surface) observed from a direction perpendicular to the light-receiving surface of the polarizing plate 1.

[0129] The inner corner 13c of the recess 13 may be a curved surface. That is, the end surface of the polarizing plate 1 located at the inner corner 13c of the recess 13 may be a curved surface. That is, the inner corner 13c of the recess may be chamfered. By making the inner corner 13c of the recess 13 a curved surface, cracks at the inner corner 13c of the recess 13 are easily suppressed. Figure 7 As shown, the corners at both ends of the recess 13 and the corners at the four corners of the polarizing plate 1 may be chamfered.

[0130] The width of the recess 13 (the width of the recess 13 in the X-axis direction) is not particularly limited, and for example, it can be greater than 3 mm and less than 160 mm. The depth of the recess 13 (the width of the recess 13 in the Y-axis direction) is not particularly limited, and for example, it can be greater than 0.5 mm and less than 160 mm. The length of the side (short side) of the polarizing plate 1 formed with the recess 13 is not particularly limited, and for example, it can be greater than 30 mm and less than 90 mm. The length of the side (long side) of the polarizing plate 1 without the recess 13 is not particularly limited, and for example, it can be greater than 30 mm and less than 170 mm.

[0131] The thickness of the entire polarizing plate 1 is not particularly limited, and may be, for example, 30 μm or more and 300 μm or less.

[0132] Figure 7 The recess 13 shown is a quadrilateral (rectangle). However, the shape of the recess 13 is not limited. For example, the recess 13 may be a square. The recess 13 may also be a polygon other than a quadrilateral or a triangle. For example, Figure 8 As shown in (a) of FIG. 1 , the shape of the recess 13 may be a semicircle. Figure 8 As shown in (b) in FIG. 1 , the shape of the recess 13 may be triangular. Alternatively, the recess 13 may be curved as a whole. Alternatively, the recess 13 may be formed by straight lines and curves. Figure 7 , Figure 8 (a) and Figure 8 The shapes of the polarizing plates 1 shown in (b) are all symmetrical, but the shape of the polarizing plates 1 may be asymmetrical. A plurality of recesses 13 may be formed on the periphery 1p of the polarizing plate 1. The plurality of recesses 13 may be formed on one side of the periphery 1p of the polarizing plate 1. The recesses 13 may be formed by cutting off at least one of the four corners of the quadrilateral polarizing plate 1.

[0133] The overall shape of the polarizing plate 1 except for the recess 13 is approximately a quadrilateral (rectangle). However, the shape of the polarizing plate 1 is not limited. For example, the shape of the polarizing plate 1 may be a square. The shape of the polarizing plate 1 may also be a polygon other than a quadrilateral, a circle, or an ellipse. The overall shape of each of the polarizing plate 2 and the optical film (3, 4) may be approximately the same as the shape of the polarizing plate 1. Figure 6In the case of the rectangular polarizing plate 1 shown, the recessed portion 13 is formed on the short side of the polarizing plate 1 , but the recessed portion 13 may be formed on the long side of the polarizing plate 1 .

[0134] like Fig. 9 As shown, the polarizing plate 1 may have a through hole in the plane in a plan view. The diameter of the through hole may be, for example, 0.5 mm to 30 mm, preferably 1 mm to 10 mm.

[0135] (Other Embodiments of Polarizing Plate)

[0136] For example, the polarizing plate may include another optical film including a resin in addition to a pair of optical films including a first optical film and a second optical film. That is, the polarizing plate may include more than three optical films. Fig.10 As shown in the figure, the polarizing plate may include a first optical film 3 and a second optical film 4, a polarizer 2 located between the first optical film 3 and the second optical film 4, and a third optical film 15 overlapping the first optical film 3. The third optical film 15 may overlap the first optical film 3 via the above-mentioned adhesive layer. The resin contained in the third optical film 15 may be at least any one of the above-mentioned resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the third optical film 15 may be the same as that of the first optical film 3. The composition of the third optical film 15 may also be different from that of the first optical film 3.

[0137] The composition of the third optical film 15 may be the same as that of the second optical film 4. The composition of the third optical film 15 may also be different from that of the second optical film 4. The thickness of the third optical film 15 may be, for example, 5 μm or more and 200 μm or less. The third optical film 15 may be peeled off and removed from the polarizing plate during the manufacturing process of the image display device. That is, the third optical film 15 may be a temporary optical film.

[0138] The polarizing plate may further include an adhesive layer overlapping one of the pair of optical films, and a release film overlapping the adhesive layer. Fig.10The polarizing plate shown may further include an adhesive layer overlapping with the second optical film 4, and a release film overlapping with the adhesive layer. The adhesive layer may include, for example, a pressure-sensitive adhesive such as an acrylic pressure-sensitive adhesive, a rubber pressure-sensitive adhesive, a silicone pressure-sensitive adhesive, or a urethane pressure-sensitive adhesive. The thickness of the adhesive layer may be, for example, greater than 2 μm and less than 100 μm. The resin contained in the release film may be at least any one of the above-mentioned resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the release film may be the same as that of the first optical film 3. The composition of the release film may also be different from that of the first optical film 3. The composition of the release film may be the same as that of the second optical film 4. The composition of the release film may also be different from that of the second optical film 4. The thickness of the release film may be, for example, greater than 10 μm and less than 100 μm. The release film may be peeled off and removed from the polarizing plate during the manufacturing process of the image display device. The release film may be disposed on both surfaces of the polarizing plate via an adhesive layer.

[0139] The polarizing plate may also have, as an optical film or layer, at least one selected from a reflective polarizing film, a film with an anti-glare function, a film with an anti-surface reflection function, a reflective film, a semi-transmitting reflective film, a viewing angle compensation film, a window film, an antistatic layer, a hard coating layer, an optical compensation layer, a touch sensor layer, and an anti-fouling layer.

[0140] <Image display device>

[0141] Polarizing plate can be used for image display device. As image display device, for example, liquid crystal display device, organic EL display device etc. can be cited. Polarizing plate can be used for polarizing plate configured on the visible side of image display device, can also be used for polarizing plate configured on the backlight side of image display device, can also be used for polarizing plate on both sides of visible side and backlight side. Because it is not easy to make the bleached part conspicuous, even if polarizing plate is used for the visible side of image display device, it is not easy to damage design. Therefore, image display device is suitable for being used as image display device with camera hole, for example, as image display device used in mobile devices such as smart phone, mobile phone and personal computer etc.

[0142] Example

[0143] The present invention will be described in further detail below using Examples. "%" and "parts" in the examples are by mass % and by mass parts unless otherwise specified.

[0144] [Thermal shock test]

[0145] The polarizing plates obtained in the examples and comparative examples were bonded to Corning glass using an adhesive layer. The glass bonded sample was placed in a thermal shock tester, and the operation of "maintaining in a tank at -40°C for 30 minutes, then instantly transferring to a tank at 85°C and maintaining for 30 minutes" was set as one cycle, and a thermal shock test was performed by repeating this operation for 100 cycles. The presence or absence of cracks was confirmed using an optical microscope.

[0146] [Determination of Boric Acid Concentration]

[0147] The borate ion (BO3 3- ) concentration distribution. Fig.11 As shown, the protective film on the side of the optical film 5 (thickness 52 μm) attached to the polarizing plate 110 is peeled off, and the separator on the adhesive layer attached to the side of the optical film 9 (thickness 21 μm) is peeled off, and one part of the end region of the corner including the concave portion is cut out with a width of 100 μm and a length of 1 mm (1000 μm) toward the inside of the polarizing plate to prepare the measurement sample 200. The measurement sample 200 sequentially comprises an optical film 201 (thickness 52 μm), an adhesive layer 202 (thickness 1 μm), a polarizer 203 (thickness 8 μm), an adhesive layer 204 (thickness 1 μm), an optical film 205 (thickness 21 μm), and an adhesive layer 206 (thickness 20 μm). The measurement area 207 in the side of the length direction (1000 μm) of the measurement sample 200 is scanned while irradiating the ion beam to obtain a two-dimensional distribution of the signal intensity of the borate ions in the side, and a portion corresponding to the side of the polarizer is cut out according to the obtained two-dimensional distribution, and the cumulative value of the signal intensity is plotted relative to the length direction of the measurement sample 200 to obtain the distribution of the boric acid concentration relative to the length direction. The conditions of time-of-flight secondary ion mass spectrometry (TOF-SIMS) are shown below.

[0148] In addition, although the boric acid concentration is measured in the state of a polarizing plate, the obtained boric acid concentration can be regarded as the boric acid concentration of the polarizer.

[0149] Device name: Product name: PHI TRIFT V nano TOF (Ulvac-Phi Co., Ltd.)

[0150] Irradiated primary ions: Au3 +

[0151] Primary ion acceleration voltage: 30kV

[0152] Spatial resolution of ion beam: 1μm×1μm

[0153] Measurement area: 200 μm × 200 μm

[0154] Based on the obtained boric acid concentration distribution, the average value of the boric acid ion strength in the range of 30 μm to 60 μm from the end is calculated, and the position from the end to where the boric acid ion strength is the above average value is defined as a low boric acid concentration portion, and the length of the region where the low boric acid concentration portion is formed from the end of the polarizing plate (the length of the low boric acid concentration portion) is measured.

[0155] [Deiodination]

[0156] The alkali-treated portion of the polarizing plate was observed by transmitted light using an optical microscope. The optical microscope image was imported into a personal computer, and the length of the region where the low iodine concentration portion was formed from the edge of the polarizing plate (the length of the low iodine concentration portion) was measured as follows.

[0157] In the optical microscope image imported into the personal computer, the low iodine concentration area appears bright and the inner area appears dark under visual observation. The optical microscope image is subjected to image processing, and the brightness of the low iodine concentration area is 180 to 220, and the brightness of the inner area is 100 to 140, and converted into a 256-level black and white image (brightness 255 is white, 0 is black), and the area with a brightness of 180 or more (white) is regarded as the low iodine concentration area to confirm whether there is a low iodine concentration area.

[0158] [Polarizer with a thickness of 8 μm]

[0159] A 20 μm thick polyvinyl alcohol film (average degree of polymerization of about 2400, saponification degree of 99.9 mol% or more) was stretched uniaxially by dry stretching to about 4.9 times, and then immersed in pure water at 60°C for 1 minute while maintaining the tension state, and then immersed in an aqueous solution of iodine / potassium iodide / water at a weight ratio of 0.05 / 5 / 100 at 28°C for 60 seconds. Thereafter, it was immersed in an aqueous solution of potassium iodide / boric acid / water at a weight ratio of 8.5 / 8.5 / 100 at 72°C for 300 seconds. Then, after washing with pure water at 26°C for 20 seconds, it was dried at 65°C to obtain a polarizer with a thickness of 8 μm in which iodine was adsorbed on the polyvinyl alcohol film and the iodine was oriented.

[0160] [Polarizing plate with a thickness of 12 μm]

[0161] A polarizing plate with a thickness of 12 μm was obtained in the same manner as the polarizing plate with a thickness of 8 μm, except that a polyvinyl alcohol film with a thickness of 30 μm was uniaxially stretched to about 5.0 times by dry stretching to obtain a polarizing plate with a thickness of 12 μm.

[0162] [Polarizing plate with a thickness of 28 μm]

[0163] A polarizing plate with a thickness of 28 μm was obtained in the same manner as the polarizing plate with a thickness of 8 μm, except that the polyvinyl alcohol film with a thickness of 75 μm was uniaxially stretched to about 4 times by dry stretching to obtain a polarizing plate with a thickness of 28 μm.

[0164] [Optical film]

[0165] COP: Cycloolefin resin film having a thickness of 23 μm (manufactured by ZEON Corporation, Japan).

[0166] TAC: 20 μm thick triacetyl cellulose film (manufactured by Konica Minolta Co., Ltd.).

[0167] [Water-based adhesive]

[0168] 3 parts of carboxyl-modified polyvinyl alcohol (KL-318 manufactured by Kuraray Co., Ltd.) were dissolved in 100 parts of water, and 1.5 parts of a polyamide epoxy additive (Sumirez Resin (registered trademark) 650 (30) manufactured by Sumika Chemtex Co., Ltd., an aqueous solution with a solid content concentration of 30%) as a water-based adhesive was added to the aqueous solution.

[0169] [Example 1]

[0170] On both sides of the 8μm polarizer, an optical film (COP film) treated with corona discharge is bonded via a water-based adhesive. An adhesive is applied to the surface of the optical film on the opposite side of the polarizer to form an adhesive layer, and a separator is bonded thereon. The separator can be peeled off from the adhesive layer. A protective film is bonded to the opposite side of the polarizer of an optical film different from an optical film having an adhesive layer. The protective film can be peeled off from the optical film. The polarizing plate obtained in this way is sliced ​​into 5.5cm squares, and a punching tool is used to perform special-shaped processing with a through hole having a diameter of 6mm.

[0171] The obtained polarizing plate was subjected to a humidification treatment in a gas phase at a temperature of 85° C. and a relative humidity of 85% for 2 hours. The polarizing plate of Example 1 was obtained in this manner. The results are shown in Table 1. It should be noted that in the polarizing plate, light leakage accompanying deiodination did not occur, and the length of the low iodine concentration portion from the end was 0 μm.

[0172] [Example 2]

[0173] A polarizing plate of Example 2 was produced in the same manner as in Example 1 except that the conditions of the humidification treatment were changed to those shown in Table 1. The results are shown in Table 1. Fig.12 The results of measuring the boric acid concentration relative to the distance from the end of the polarizing plate are shown in FIG. Fig.13 The deiodination observation results are shown in FIG.

[0174] [Example 3]

[0175] A polarizing plate of Example 3 was produced in the same manner as in Example 1 except that the conditions of the humidification treatment were changed to those shown in Table 1. Table 1 shows the results.

[0176] [Comparative Example 1]

[0177] A polarizing plate of Comparative Example 1 was produced in the same manner as in Example 1 except that the conditions of the humidification treatment were changed to those shown in Table 1. Table 1 shows the results.

[0178] [Comparative Example 2]

[0179] A polarizing plate of Comparative Example 2 was produced in the same manner as in Example 1 except that the conditions of the humidification treatment were changed to those shown in Table 1. Table 1 shows the results.

[0180] [Comparative Example 3]

[0181] A polarizing plate of Comparative Example 3 was prepared in the same manner as in Example 1 except that the humidification treatment was not performed but the plate was immersed in warm water at a temperature of 74° C. for 16 minutes. The results are shown in Table 1. The deiodination observation results are shown in Table 1. Fig.14 In this polarizing plate, a low iodine concentration region is generated due to deiodination, and its length is about 250 μm.

[0182] [Table 1]

[0183]

[0184] *1Not humidification treatment, but immersion in 74℃ warm water for 16 minutes.

[0185] [Example 4]

[0186] A corona-discharge treated optical film COP was bonded to one side of a 12 μm polarizer via a water-based adhesive, and a corona-discharge treated optical film TAC was bonded to the other side via a water-based adhesive to produce a polarizing plate. The obtained polarizing plate was sliced ​​into 5.5 cm squares and subjected to profile processing with through holes of 6 mm in diameter.

[0187] The obtained polarizing plate was subjected to a humidification treatment in which the polarizing plate was kept in a gas phase at a temperature of 85° C. and a relative humidity of 85% for 2 hours. A polarizing plate of Example 4 was obtained in this manner. The results are shown in Table 2.

[0188] [Example 5]

[0189] A polarizing plate of Example 5 was produced in the same manner as in Example 4 except that the conditions of the humidification treatment were changed to the conditions shown in Table 2. Table 2 shows the results.

[0190] [Comparative Example 4]

[0191] A polarizing plate of Comparative Example 4 was produced in the same manner as in Example 4 except that the conditions of the humidification treatment were changed to those shown in Table 2. Table 2 shows the results.

[0192] [Comparative Example 5]

[0193] A polarizing plate of Comparative Example 5 was produced in the same manner as in Example 4 except that the conditions of the humidification treatment were changed to those shown in Table 2. Table 2 shows the results.

[0194] [Comparative Example 6]

[0195] A polarizing plate of Comparative Example 6 was produced in the same manner as in Example 4 except that the conditions of the humidification treatment were changed to those shown in Table 2. Table 2 shows the results.

[0196] [Table 2]

[0197]

[0198] *1Not humidification treatment, but immersion in 74℃ warm water for 16 minutes.

[0199] [Comparative Example 7]

[0200] A corona-discharge treated optical film COP was bonded to one side of a 28 μm polarizer via a water-based adhesive, and a corona-discharge treated optical film TAC was bonded to the other side via a water-based adhesive to produce a polarizing plate. The obtained polarizing plate was sliced ​​into 5.5 cm squares and subjected to profile processing with through holes of 6 mm in diameter.

[0201] The obtained polarizing plate was subjected to a humidification treatment in a gas phase at a temperature of 85° C. and a relative humidity of 85% for 2 hours. A polarizing plate of Comparative Example 7 was obtained in this manner. The results are shown in Table 3 together with the results of Examples 1 and 2.

[0202] [Comparative Example 8]

[0203] A polarizing plate of Comparative Example 8 was produced in the same manner as in Comparative Example 7 except that the conditions of the humidification treatment were changed to those shown in Table 3. The results are shown in Table 3 together with the results of Examples 1 and 2.

[0204] [Table 3]

[0205]

[0206] *1Not humidification treatment, but immersion in 74℃ warm water for 16 minutes.

[0207] Description of Reference Numerals

[0208] 1 polarizing plate, 2, 7 polarizing plate, 3, 5 first optical film, 4, 9 second optical film, 10 first laminate, 13 recess, 14 through hole, 15 third optical film, 20 image display device, 21 polarizing plate, 22 camera hole, 23 liquid crystal panel 24 cover glass, 25 adhesive layer, 26 polarizing plate, 27 camera, 28 light-shielding tape, 30 low boric acid concentration area, 31 middle area, 32 inner area, 50 end mill, 50e blade (edge), 100 second laminate, 110 polarizing plate, 200 measurement sample, 201, 205 optical films, 202, 204 adhesive layer, 203 polarizing plate, 206 adhesive layer, 207 measurement area, α helix angle, β cutting angle.

Claims

1. A method for manufacturing a polarizing plate, comprising: A first lamination step of laminating optical films on both sides of a polarizing plate having a thickness of 15 μm or less to produce a first laminate; as well as In a humidification treatment step, the first laminate is kept in a gas phase at a temperature of 35° C. or higher and a relative humidity of 75% RH or higher for 0.5 hour or more and 4 hours or less, In the first laminate, the polarizer is located between the first optical film and the second optical film. The first optical film and the second optical film both contain a cyclic olefin polymer resin.

2. The method for manufacturing a polarizing plate according to claim 1, wherein: The method further includes a forming step of forming the first stacked body before the humidification step.

3. The method for manufacturing a polarizing plate according to claim 2, wherein: In the forming step, a deformed portion is formed in the first stacked body.

4. The method for manufacturing a polarizing plate according to claim 2 or 3, wherein: The method further includes a cutting step of cutting the first stacked body before the humidification step.

5. The method for manufacturing a polarizing plate according to claim 4, wherein: In the cutting step, the first laminate is cut so that the position of the end of the optical film is the same as the position of the end of the polarizing plate in a plan view of the first laminate.

Citation Information

Patent Citations

  • Polarizer, polarizing plate and production method of the polarizer

    JP2016206641A

  • Polarizing plate with adhesive and image display device

    CN110133784A

  • Manufacturing method of polarizing plate, polarizing plate, and image display apparatus using polarizing plate

    JP2006023573A